1970
DOI: 10.3329/ujzru.v27i0.1959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, body weight, body condition and scrotal circumference on sperm abnormalities of bulls used for artificial insemination (AI) programme in Bangladesh

Abstract: Impacts of age, body weight, body conditions, and scrotal circumference on sperm abnormalities of bulls used for artificial insemination (AI) in Bangladesh have been studied. During 1997During -2002During , 1390 ejaculates of semen from 71 bulls from Central Cattle Breeding Station and Dairy Farm, Savar, Dhaka, Rajshahi Dairy and Cattle Improvement Farm, Rajabarihat, and District Artificial Insemination Centre, Rajshahi, were collected and examined. Total head abnormalities, free loose head, mid-piece, tail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
(2 reference statements)
3
9
0
1
Order By: Relevance
“…The cause of idiopathic infertility may be a high index of DNA fragmentation in chromatin [57][58][59][60][61]. The DNA fragmentation in spermatozoa also depends on numerous biotic and abiotic factors [62][63][64][65][66][67][68][69].…”
mentioning
confidence: 99%
“…The cause of idiopathic infertility may be a high index of DNA fragmentation in chromatin [57][58][59][60][61]. The DNA fragmentation in spermatozoa also depends on numerous biotic and abiotic factors [62][63][64][65][66][67][68][69].…”
mentioning
confidence: 99%
“…Similarly, Sarder [34] pointed that, there were no significant effects of body condition score of bulls on some semen characteristics. Meanwhile, Addass [35] reported that, there were significant effects of body condition score of bulls on sperm production potential and scrotal circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm morphology was evaluated using a protocol developed by Sarder (2008). Smears of fresh semen were air-dried and fixed in absolute alcohol for 3 min and then stained with William's stain for 5 min.…”
Section: Semen Collection and Evaluationmentioning
confidence: 99%
“…Stock solution III consisted of 10 ml stock solution I and 170 ml of 5% phenol. 25 ml of Stock solution II and 50 ml of stock solution III were mixed to produce the final staining solution, which was filtered before use (Sarder, 2008). After staining, the slides were washed in running tap water, dried and examined using bright field light microscopy at a magnification of x1000.…”
Section: Semen Collection and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation